Agroforestry systems in the semi-arid region of Minas Gerais - Barbosa, Erika Aparecida Ferreira; Santos, Bruna Myrela de Almeida; Silva, Gustavo Pereira da; Martins , Ernane Ronie; Ribeiro, Aureo Eduardo Magalhães (Seven Editora, 2024)
Environmental education plays a fundamental role in contributing to the formation of conscious citizens who can understand the relationship between humans and the natural environment. To achieve this, it is important to have the necessary means tobuild effective changes that contribute to the autonomy of the population in the Semiarid region. In view of this, university extension plays an important role in the inclusion of values, skills, knowledge, responsibilities and aspects that promote improvement in the quality of life of society. In this context, the objective of this report is to describe the activities carried out in the workshop "Agroforestry Systems in the Semiarid Region of Minas Gerais" held at the Tabocal Agricultural Family School (EFAT) in the municipality of São Francisco-MG. The workshop was conducted by undergraduate students from the Federal University of Minas Gerais’ Agronomy program, and the following topics were covered: the definition of Agroforestry Systems (AFS); the difference between AFS and agricultural intercropping; the importance of AFS for food production; advantages and disadvantages; and management and implementation. The workshop was conducted dynamically and with active participation from the students, through questions and ideas raised, facilitating more in-depth discussions on the subjects. DOI:https://doi.org/10.56238/sevened2023.001-011